Dominant Risk Factors For Coronary Heart Disease In Patients Aged - Nengke Puspita Sari (Jurnal Riset Media Keperawatan, 2026)
Background: Coronary heart disease (CHD) has traditionally been associated with older adults, but its incidence among individuals aged <45 years is increasing globally. Modifiable risk factors such as smoking, hypertension, dyslipidemia, physical inactivity, and psychosocial stress are suspected to contribute significantly to early-onset CHD. However, evidence regarding the dominant risk factors in young adults from resource-limited regions such as Bengkulu remains limited. Identifying the most influential risk factors is essential for designing targeted prevention strategies. Method: This study employed a quantitative approach using a case-control design. A total of 120 participants (60 cases of CHD aged <45 years and 60 controls without CHD, matched by age and sex) were recruited from RSUD M Yunus Bengkulu. Data on smoking, hypertension, diabetes mellitus, dyslipidemia, family history of CHD, physical activity, and stress level (measured by Perceived Stress Scale-10/PSS-10) were collected through medical records and structured interviews. Bivariate analysis used chi-square tests, while multivariate analysis used logistic regression to determine dominant risk factors (adjusted odds ratio/AOR) with a significance level of p<0.05. Results: Bivariate analysis showed that smoking (p=0.001; OR=4.2), hypertension (p=0.003; OR=3.8), dyslipidemia (p=0.002; OR=3.9), physical inactivity (p=0.010; OR=2.9), and high stress (p=0.001; OR=4.5) were significantly associated with CHD in patients aged <45 years. Multivariate logistic regression identified high stress (AOR=5.1; 95% CI: 2.12–12.42; p=0.001) and smoking (AOR=4.5; 95% CI: 1.90–10.64; p=0.001) as the dominant risk factors after controlling for confounding variables. Hypertension and dyslipidemia remained significant but with lower AOR values, while diabetes mellitus and family history were not statistically significant. Conclusion: High stress and smoking are the dominant risk factors for coronary heart disease among patients aged <45 years at RSUD M Yunus Bengkulu. These findings suggest that cardiovascular prevention programs for young adults should prioritize smoking cessation interventions and stress management strategies. Community-based screening for stress and tobacco use, integrated into primary healthcare services, is strongly recommended.